Role of mitophagy in breast cancer: mitophagy-apoptosis balance and reactive oxygen species play determining role - Yiu, Lung; Chong, Yan Wah; Yan, Shuyi; Tsang, Suk Ying (Frontiers in Physiology, 2026)
This review aims to present a current overview of the role of mitophagy in breast cancer progression, especially from the point of view of when the cancer is in the untreated state or under chemotherapeutic treatment. We aim to explain the apparently contradictory results as reported in numerous studies on the differential role of mitophagy in breast cancer. We propose that different levels of reactive oxygen species (ROS), and the balance between mitophagy and apoptosis under different conditions are the major reasons to explain for the “discrepancy”. If the cancer cells are untreated, a medium level of ROS promotes cancer progression. Mitophagy inhibition, which leave the dysfunctional mitochondria to generate more ROS, would therefore increase cancer progression. On the other hand, if the cancer cells are undergoing chemotherapeutic treatment, the excessively high level of ROS generated would stimulate both mitophagy and apoptosis, where mitophagy would inhibit apoptosis. In this case, inhibiting mitophagy would potentiate apoptosis and therefore enhance treatment effectiveness. The molecular mechanisms underlying the regulation between mitophagy and apoptosis are also discussed in this review. In summary, the review shall provide important insights for the role of mitophagy in breast cancer. It is proposed that the identification of the molecules involved in balancing mitophagy and apoptosis, and combined therapeutic strategies are the key areas for future exploration.